ANALISIS IMPLEMENTASI PROGRAM IMUNISASI DASAR LENGKAP DALAM UPAYA CAPAIAN UNIVERSAL CHILD IMMUNIZATION - Syukriadi; Kiswanto; Jasrida Yunita (Journal of Hospital Administration and Management (JHAM), 2026)
Complete Basic Immunization is an effective public health intervention to prevent vaccine-preventable diseases and support the achievement of Universal Child Immunization (UCI). However, UCI coverage in Rokan Hulu Regency has remained below the established target in recent years. This study aimed to analyze the implementation of the Complete Basic Immunization program in achieving Universal Child Immunization in Rokan Hulu Regency. A qualitative study with a descriptive approach was conducted. Twelve informants were selected purposively, including immunization program managers at the District Health Office, heads of primary healthcare centers, immunization officers, and community health volunteers. Data were collected through in-depth interviews, observations, and document reviews, and analyzed using data reduction, data display, and conclusion drawing techniques. Source and method triangulation were employed to ensure data validity. The findings revealed that program communication was generally well implemented through socialization activities and cross-sectoral coordination. Human resources were considered adequate in terms of quantity and competence; however, limited funding and the absence of specific incentives for program implementers remained challenges. Facilities and infrastructure were generally available, although shortages of vaccine cold-chain supporting equipment were identified. In addition, social, cultural, religious, and geographical factors influenced program implementation. The study concludes that the implementation of the Complete Basic Immunization program in Rokan Hulu Regency has been relatively effective, but strengthening budget support, enhancing cross-sectoral collaboration, and improving community education are still required to increase Universal Child Immunization coverage.